1992
DOI: 10.1002/j.1460-2075.1992.tb05314.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative membrane receptor for the bioactive phospholipid, lysophosphatidic acid.

Abstract: Lysophosphatidic acid (LPA) is a naturally occurring phospholipid with hormoneand growth factor-like activities. Exogenous LPA stimulates GTP-dependent phosphoinositide hydrolysis and inhibits adenylate cyclase in its target cells, but the site of action of LPA is unknown. We now report the identification by photoafTinity labeling of a putative LPA membrane receptor in various LPA-responsive cell types. A 32p_ labeled LPA analogue containing a photoreactive fatty acid, [32P]diazirine-LPA, labels a membrane pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(109 citation statements)
references
References 27 publications
6
103
0
Order By: Relevance
“…4) demonstrated that the LPAAT message is expressed at very high levels in the liver and pancreas, at low levels in the placenta and certain regions of the brain, and at intermediate levels in numerous other tissues. This pattern of expression is in marked contrast to the pattern seen with the LPA receptor, which is expressed most abundantly in the brain, not in the liver, and at intermediate levels in other tissues (7,8). This suggests the possibility that, at least in the brain and liver, LPA signaling and metabolism are mediated by additional receptors and enzymes.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…4) demonstrated that the LPAAT message is expressed at very high levels in the liver and pancreas, at low levels in the placenta and certain regions of the brain, and at intermediate levels in numerous other tissues. This pattern of expression is in marked contrast to the pattern seen with the LPA receptor, which is expressed most abundantly in the brain, not in the liver, and at intermediate levels in other tissues (7,8). This suggests the possibility that, at least in the brain and liver, LPA signaling and metabolism are mediated by additional receptors and enzymes.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, LPA is a potent promoter of tumor cell growth and invasion (5,6). LPA exerts its biological effects via at least one, but perhaps multiple, specific G protein-coupled receptors (7)(8)(9). Engagement of the receptor results in activation of Ras and the Raf/mitogen-activated protein kinase pathway, stimulation of phospholipases C and D, inhibition of adenylyl cyclase, and tyrosine phosphorylation of focal adhesion proteins along with actin cytoskeleton remodeling (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the evidence supports the view that this simple phospholipid interacts directly with receptors on the surface of cells, rather than by acting as a general membrane perturbant, or as a precursor of intracellular metabolites. Thus photoaffinity-labelling studies with a LPA analogue have identified a binding protein of apparent molecular mass 38-40 kDa in a range of cell types, including fibroblasts [6]. Binding of LPA to this protein was inhibited by suramin, a polysulphonated naphthylurea derivative that also blocks the biological response of intact cells to LPA [7].…”
Section: Introductionmentioning
confidence: 99%
“…One previous study reported the synthesis and characterization of a photoreactive LPA analogue containing a trifluoromethylphenyldiazirine group for labeling of fetal bovine serum and LPA responsive cells. 19 In this paper, we report the syntheses of additional photoactivable analogues of acyland O-alkyl-linked LPAs in which the long chain resembles an oleoyl (ester) or oleyl (ether) chain, respectively. The rationale for this approach is that the oleoyl chain has been shown to represent the maximally effective fatty acyl chain of natural LPAs in previous structure-activity studies.…”
Section: Introductionmentioning
confidence: 99%